If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 = 9x + 11 + -7x Reorder the terms: 6 + 7x = 9x + 11 + -7x Reorder the terms: 6 + 7x = 11 + 9x + -7x Combine like terms: 9x + -7x = 2x 6 + 7x = 11 + 2x Solving 6 + 7x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 7x + -2x = 11 + 2x + -2x Combine like terms: 7x + -2x = 5x 6 + 5x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 5x = 11 + 0 6 + 5x = 11 Add '-6' to each side of the equation. 6 + -6 + 5x = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 11 + -6 5x = 11 + -6 Combine like terms: 11 + -6 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 3squared-2(11-8)squared=36x | | 4/3x=1/10 | | 10y-3y= | | 2x^3+6x^2+3x+9=0 | | -24=36+49x | | 0.5(x+90)+1.3x=126 | | 17x=44+13x | | 1=1+w | | 6(3n+6-2n)-26-3n=20+26-2*3*2 | | Xy^2-36x=0 | | 8p+2=8+7p | | -5y-15=4y+12 | | 8*y^2-72=0 | | 20(37x+20x)=7.06 | | 1.6=p/7 | | -5(9+X)= | | 2x^2+5x-10=y | | ln(8)-ln(2)= | | X^2+52x+100=0 | | 11xsquared-9x=0 | | (7-2)(5-8)= | | 3(4x-12)=12(x+3) | | (8X^2-2X+7)-(2X^2-4X-7)=0 | | 45+15y=y | | 2x+26y=3x+21y | | 9y^2-49r^2=0 | | 0=(5x-31)(x)-75 | | -2.8y=3.08 | | 10+25x=5(5x+3) | | 3128=34.08x | | ln(x-5)=lnx-ln*5 | | 24x+6= |